Perception Teacher to leadership Principal SDN 13 Surau Gadang - Nur Halimahturrafiah; Fitra Dewi; Nurhizrah Gistituati (Bisma The Journal of Counseling, 2022)
The purpose of this study was to determine the teacher's perception of the leadership of the principal of the State Elementary School 13 Surau Gadang seen from influencing, moving and motivating. This research includes descriptive research, the population is 16 people who teach at SDN 13 Surau Gadang. The sampling technique used is total sampling. The instrument uses a questionnaire/questionnaire. Research results In general, the teacher's perception of the leadership of the Principal of the State Elementary School 13 Surau Gadang is on an average score of 4.5 with a good category. This means that the leadership at the State Senior High School 1 Lembah Melintang has been going well. That the principal's leadership must be able to encourage the performance of teachers by showing a sense of friendship, closeness, and consideration for teachers, both as individuals and as groups.